Managing unused, damaged, and expired medications: Knowledge and attitudes among people of Malang, Indonesia - Hananditia Rachma Pramestutie, Ayuk Lawuningtyas Hariadini, Tamara Gusti Ebtavanny, Ratna Kurnia Illahi, Shafira Nur Ilmi (Journal of Applied Pharmaceutical Science, 2021)
The high rate of medicine storage must be balanced with knowledge and attitudes for proper management of medications, specifically the storage and disposal of medications in order to prevent problems in the scope of healthcare and the environment. This study aimed to find out the relationship between the level of knowledge and attitudes among people of the Greater Malang area in managing leftover, damaged, and expired medications. This research is an analytic observational research. The sample of this research is people in the Greater Malang area who were selected with convenience sampling according to the inclusion and exclusion criteria. The utilized instrument in this research was a questionnaire on the knowledge and attitudes in managing leftover, damaged, and expired medications. Data were processed with the Spearman correlation statistical testing. The research results indicated that, for the level of knowledge among people of the Greater Malang area in managing leftover, damaged, and expired medications, 58% were in the fair category. For attitudes, 52% were negative. There was no relationship between the level of knowledge and attitudes of the people in managing leftover, damaged, and expired medications (p = 0.076). Pharmacists need to continuously educate the public about the storage and disposal of leftover, damaged, and expired medications.
Keywords: Knowledge, attitude, leftover medicine, damage medicine, expired medicine